The Representation of Whiteness in Ralph Ellison - Alya Zulfikar (Passage, 2019)
Racism has always been a never-ending issue in society; one specific racist act is whiteness. The issue of whiteness is still considered an inevitable issue that is still happening until today, and it gives negative impact on the non-white. The issue of racism is often analyzed as a form of prejudice, stereotype, and discrimination. However, the issue of racism is a general issue. Thus, the present research attempts to portray the specific act of racism, which is whiteness. The novel Invisible Man (1952) by Ralph Ellison brings the issue of racism. By using Garner (2007) theory of whiteness, the issue of racism that is present in the novel is analyzed under the four themes of whiteness to provide an alternative understanding of the issue of racism through the lens of whiteness. This research entitled “The Representation of Whiteness in Ralph Ellison’s Invisible Man” attempts to reveal how whiteness is constructed as a racist act in the society which becomes the central issue of the novel. This research employs Young’s (1999) theory of representation and Garner’s (2007) theory of whiteness to provides another perspective of whiteness by portraying the themes of whiteness, and how it is constructed in society. The findings show that the issue of whiteness is dominantly exercised through terror and supremacy, and it makes the non-white feel inferior to the White. Keywords: whiteness, white privilege, white supremacy